Histidine-226 is part of the pH sensor of NhaA, a Na+/H+ antiporter in Escherichia coli. - Gerchman, Y (1993)
The nhaA gene of Escherichia coli, which encodes a pH-activated Na+/H+ antiporter, has been modified; six of its eight histidine codons were mutated to arginine codons by site-directed mutagenesis, yielding the mutations H254R-H257R (a double mutant), H226R, H39R, H244R, and H319R. In addition a deletion (delta nhaA1-14) lacking the remaining two histidines, His-3 and His-5, has been constructed. By comparing the phenotypes conferred by plasmids bearing the various mutations to the phenotype of the wild type upon transformation of strains NM81 (delta nhaA) or EP432 (delta nhaA, delta nhaB) we found that none of the NhaA histidines are essential for the Na+/H+ antiporter activity of the NhaA protein. However, the replacement of His-226 by Arg markedly changes the pH dependence of the antiporter. All mutants except H226R confer to NM81 and EP432 Na+ resistance up to pH 8.5 as well as Li+ resistance. Cells bearing H226R are resistant to Li+ and to Na+ at neutral pH, but they become sensitive to Na+ above pH 7.5. Analysis of the Na+/H+ antiporter activity of membrane vesicles derived from H226R cells shows that the mutated protein is activated by pH to the same extent as the wild type. However, whereas the activation of the wild-type NhaA occurs between pH 7 and pH 8, that of H226R antiporter occurs between pH 6.5 and pH 7.5. Furthermore, while the wild-type antiporter remains almost fully active at least up to pH 8.5, H226R is reversibly inactivated above pH 7.5, reaching 10-20% of the maximal activity at pH 8.5. We suggest that His-226 is part of a pH-sensitive site that regulates the activity of NhaA.